1998
DOI: 10.1136/thx.53.9.768
|View full text |Cite
|
Sign up to set email alerts
|

Exertional dyspnoea in patients with airway obstruction, with and without CO2 retention

Abstract: Background-Dyspnoea is a common and disabling symptom in patients with cardiopulmonary disease. Unfortunately the mechanisms that produce dyspnoea are still poorly understood. The relationship between dyspnoea and the load on the ventilatory muscles, chemical drive, and ventilatory indices was therefore assessed in patients with obstructive pulmonary disease during an incremental exercise test. Methods-Fifty patients with a wide range of obstructive pulmonary disease (mean forced expiratory volume in one secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
(19 reference statements)
1
8
1
Order By: Relevance
“…This unexpected finding could be explained by the higher intensity of exercise in the non-FL patients (table 3) and, consequently, the different ventilatory demand at which the two groups were compared (table 2). These data are also consistent with the results of KILLIAN et al [28] and CLOOSTERMAN et al [23] who found that many patients with very severe COPD stopped exercise primarily because of leg fatigue rather than dyspnoea. The higher leg fatigue Borg scores at peak exercise in the present FL patients probably reflect muscle weakness due to deconditioning and/or muscle dysfunction [29,30].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This unexpected finding could be explained by the higher intensity of exercise in the non-FL patients (table 3) and, consequently, the different ventilatory demand at which the two groups were compared (table 2). These data are also consistent with the results of KILLIAN et al [28] and CLOOSTERMAN et al [23] who found that many patients with very severe COPD stopped exercise primarily because of leg fatigue rather than dyspnoea. The higher leg fatigue Borg scores at peak exercise in the present FL patients probably reflect muscle weakness due to deconditioning and/or muscle dysfunction [29,30].…”
Section: Discussionsupporting
confidence: 82%
“…In patients with CO 2 retention, the changes in VT/tI from rest to peak exercise were smaller than in the subjects without CO 2 retention, but their concurrent increase in neuromuscular inspiratory drive was significantly greater. According to the present results, the COPD patients of CLOOSTERMAN et al [23] who exhibited CO 2 retention during peak exercise, should mainly represent individuals who exhibited FL at rest, supporting the notion that increased inspiratory load, rather than neuromuscular inspiratory drive, limits VT,max (and hence ventilation) in COPD patients who exhibited FL at rest. In fact, it is likely that during heavy exercise a ceiling effect occurs in patients with severe COPD, making the inspiratory reserve volume impossible to be lowered further.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations